2011
DOI: 10.1016/j.econmod.2011.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Investigating regional house price convergence in the United States: Evidence from a pair-wise approach

Abstract: In this paper we examine long-run house price convergence across US states using a novel econometric approach advocated by Pesaran (2007) and Pesaran et al. (2009). Our empirical modelling strategy employs a probabilistic test statistic for convergence based on the percentage of unit root rejections among all state house price differentials. Using a sieve bootstrap procedure, we construct confidence intervals and find evidence in favour of convergence. We also conclude that speed of adjustment towards long-run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 39 publications
4
74
0
2
Order By: Relevance
“…Holmes et al (2011) note that there is scant evidence of a long-run equilibrium house price relationship in the USA, but they concur with other authors that there is house price diffusion among neighbouring but not non-neighbouring tracts (Barros et al, 2012;Dolde & Tirtiroglu, 1997;Kim & Rous, 2012;Pollakowski & Ray, 1997). Oikarinen (2006) concludes that housing price changes in Finland diffuse from the Helsinki Metropolitan Area to regional centres and then to the peripheral areas.…”
Section: House Price Diffusion Elsewheresupporting
confidence: 60%
“…Holmes et al (2011) note that there is scant evidence of a long-run equilibrium house price relationship in the USA, but they concur with other authors that there is house price diffusion among neighbouring but not non-neighbouring tracts (Barros et al, 2012;Dolde & Tirtiroglu, 1997;Kim & Rous, 2012;Pollakowski & Ray, 1997). Oikarinen (2006) concludes that housing price changes in Finland diffuse from the Helsinki Metropolitan Area to regional centres and then to the peripheral areas.…”
Section: House Price Diffusion Elsewheresupporting
confidence: 60%
“…Apergis & Payne, 2012;Holmes, Otero, & Panagiotidis, 2011). Switzerland is a small and stable economy with a high population density and rather homogeneous mortgage financing availability.…”
Section: Discussionmentioning
confidence: 99%
“…Holmes et al examined long-run house price convergence across US states using a pair-wise approach. This study showed that long-run house price convergence was present across US states and Metropolitan [21]. Holmes et al examined long-run house price convergence across the twenty Paris districts using a quarterly dataset that spans from 1991 to 2014.…”
Section: Literature Reviewmentioning
confidence: 99%